The Design of ACE (Aluminum Corrosion and Electrolysis) Reactor and Its Performance to Produce Hydrogen from Beverage Cans - Ahmad Zikri; Erlinawati .; Lety Trisnaliani; Daya Wulandari (Reaktor, 2017)
AbstractThe reaction of aluminum (Al) with an alkaline solution in producing hydrogen gas has been known for a long time. This aluminum corrosion reaction has a major obstacle in the passivation phenomenon, a formation of aluminum oxide coating on the metal surface that prevents aluminum from collapsing. Integration of electric current to the potassium hydroxide solution could result in electrolysis of water which increases the production of hydrogen. This process was carried out continuously in an ACE (aluminum corrosion and electrolysis) reactor of water. This reactor design enabled to produce hydrogen and oxygen in separating chamber. The use of 10 g of cans, 0.02 M gallium, 12 VDC, and 0.8 M KOH obtained the maximum production rate of hydrogen 162.58 ml/s with a purity of 79.83%. Keywords: aluminum corrosion; hydrogen; water electrolysis